Sonograms of perineal muscles as a noninvasive diagnosis of pyometra and endometritis in beef cows: a preliminary study - Amrozi; S. Y. Hayanti; Aryogi; D. Pamungkas; D. M. Dikman; E. Handiwirawan; F. A. Pamungkas; Herdis; Jakaria; M. F. Ulum (Archives Animal Breeding)
Changes in reproductive status affect the perineal muscles. These modifications enable the noninvasive diagnosis of pyometra and mastitis in beef cows. This study aims to assess the thickness and intensity of the coccygeus and levator ani muscles in beef cows affected by the reproductive disorders of pyometra and mastitis. The sample consisted of 59 Bali beef cows, 75 Madura beef cows, and 71 Ongole cross beef cows. The cervical organs, uterine corpus, uterine cornua, and placenta were visualized using transrectal imaging. The resulting images were categorized into two groups: a control group (with nonpregnant nonpartum, pregnant, and nonpregnant postpartum statuses) and a group with reproductive disorders. The coccygeus and levator ani muscles were visualized using transcutaneous imaging. Pregnant Bali beef cows have thicker coccygeus muscles than nonpregnant nonpartum Bali beef cows (P<0.05). Pregnant Madura beef cows have thicker coccygeus muscles than nonpregnant nonpartum and nonpregnant postpartum Madura beef cows (P<0.05). Pregnant Madura beef cows have thicker levator ani muscles than nonpregnant postpartum Madura beef cows (P<0.05). Nonpregnant nonpartum and pregnant Ongole cross beef cows have thicker coccygeus and levator ani muscles than nonpregnant nonpartum and pregnant Bali and Madura beef cows. For pyometra, Bali, Madura, and Ongole cross beef cows have thicker coccygeus and levator ani muscles than endometritis, nonpregnant nonpartum, pregnant and nonpregnant postpartum Bali, Madura, and Ongole cross beef cows. In the control group, only the levator ani muscle of pregnant Bali beef cows had a significant intensity compared to nonpregnant postpartum Bali beef cows (P<0.05). The muscle intensity of the coccygeus and levator ani of nonpregnant nonpartum, pregnant, and nonpregnant postpartum Bali beef cows was higher than nonpregnant nonpartum, pregnant, and nonpregnant postpartum groups for Madura and Ongole cross beef cows. For pyometra, Bali, Madura, and Ongole cross beef cows had higher coccygeus muscle intensity than nonpregnant nonpartum and pregnant Bali, Madura, and Ongole cross beef cows. Reproductive status and disorders affect the diameter of the reproductive tract and plecentome, which affect changes in sonogram thickness and intensity of the coccygeus and levator ani muscles.